SUSTAINABILITY STATUS OF BELAT FISHING TOOLS BASED ON ECOLOGICAL, TECHNOLOGICAL AND SOCIAL ASPECTS IN MERBAU DISTRICT, RIAU PROVINCE - Brown, Arthur; Fadhli, Rezky; Zain, Jonny (Asian Journal of Aquatic Sciences, 2024)
This research was carried out in November 2022 in Merbau District, Meranti Islands Regency, Riau Province, to determine the sustainability status of the belat fishing gear based on ecological, social and technological aspects. The method used in this research is a survey method, while purposive sampling is used to determine respondents. Data collection was carried out through observation, interviews and documentation directly with two academics from the UNRI Faculty of Fisheries and Marine, two people from the Meranti Regency Fisheries Service, four capture fisheries entrepreneurs (traders and collectors), two fishermen group leaders, and ten fishermen. The research results show a decrease in the number of belat fishing gear every year; in 2020, the number of belat fishing gear was 65 units, and in 2022, the number of belat fishing gear was nine units. Belat fishing gear is not selective, as seen from the leverage analysis that has been carried out with a sensitivity attribute value of 40.53. Belat can catch small fish that are not yet suitable for catching. The sustainability status of belat fishing gear is seen through the attribute values ​​of three dimensions. The sustainability index value for the ecological dimension of the belat fishing gear is 51.11, meaning it is pretty sustainable. The sustainability index value of the technological dimension in fishing using belat fishing gear is 40.53, which is classified as less sustainable. The index value of the social dimension in fishing using the belat fishing gear is 59.99, meaning it is in the reasonably sustainable category.